TPG image compression technology - Shitao WANG; Piao DING; Xiaozheng HUANG; Haijun LIU; Binji LUO; Xinxing CHEN; Youbao WU; Ronggang WANG (Dianxin kexue)
TPG(tiny portable graphic) is a new image compression technology based on the video part of AVS2 standard,whose compression efficiency is notably higher than traditional image formats like JPG,PNG and GIF.Theory and feature of TPG image compression technology were introduced.Then,the compression efficiency of TPG and traditional image formats was compared.Results show that TPG has overwhelming advantage.